PENGARUH AGENCY COST DAN SIKLUS KEHIDUPAN PERUSAHAAN TERHADAP KEBIJAKAN DIVIDEN PADA PERUSAHAAN TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2009-2011 - Junius Menafati Waruwu; Muhammad Nuryatno Amin (Jurnal Akuntansi Trisakti, 2014)
The objective of this research is to examine the effect of agency cost (proxied by insider ownership, dispersion of ownership and institutional ownership) and life cycle of company to dividend policy in public listed companies actively traded in Indonesian Stock Exchange. The nature of the study was hyphothesis descriptive method with quantitative approach. Sample in this study were 58 companies for a period of 2009 to 2011. Data used were secondary data from annual financial reports. While the method of used in this study is purposive sampling and the model analysis is simple linear regression. The result of the study indicates that institutional ownership variable has the effect to dividend policy, while insider ownership, dispersion ownership and life cycle of company have no effect to dividend.